Membudayakan Kepemimpinan Transformasional di Lembaga Pendidikan Islam - Abadullah Rosyaad; Binti Maunah; Achmad Patoni (Jurnal Budi Pekerti Agama Islam, 2024)
The transformational leadership style with the relational relationship model used will foster trust in followers which is capital for the growth and development of sharing knowledge. The results of research from Lowe et.al in 1996 on 39 transformational leadership studies conducted in various countries showed that transformational leadership was effective. This research aims to find the concept of cultivating transformational leadership in Islamic Education Institutions. Research result; 1) The cultivation of transformational leadership in Islamic educational institutions can be carried out based on centralized policies with a structured coercive approach either through official policies, guidebooks for heads of educational institutions or simply appeals supported by the practice of transformational leadership behavior by leaders above as a model; 2) The cultivation of transformational leadership in Islamic educational institutions can also be done using an awareness approach where every leader of an educational institution at every level is enlightened regarding the concept and practice of transformational leadership along with its advantages and disadvantages so that they are made aware of implementing transformational leadership; 3) In the context of educational institutions that adhere to a semi-centralized system such as in Indonesia with a pragmatic character possessed by the majority of madrasah and department heads, the first approach is more effective in cultivating transformational leadership throughout existing Islamic educational institutions.